Uncovering pseudogenes and intergenic protein-coding sequences in TriTryps’ genomes - Abrahim, Mayla (2022)
Fundação Oswaldo Cruz. Vice-Diretoria de Desenvolvimento Tecnológico, Bio-Manguinhos. Instituto de Tecnologia em Imunobiológicos. Laboratório de Tecnologia Imunológica. Rio de Janeiro, RJ, Brasil.